Propofol Target-Controlled Infusion in Emergency Department Sedation (ProTEDS): a multicentre, single-arm feasibility study. Issue 3 (9th December 2020) - Burton, Fiona Marie; Lowe, David John; Millar, Jonathan; Corfield, Alasdair R; Watson, Malcolm J; Sim, Malcolm A B
Abstract : Background: Procedural sedation is a core skill of the emergency physician. Bolus administration of propofol is widely used in UK EDs. Titrated to an end point of sedation, it has a rapid effect but has been associated with adverse incidents. The use of a target-controlled infusion (TCI) of propofol is not routine but may reduce the incidence of adverse incidents. The primary aims of this single-arm feasibility study were patient satisfaction and to establish recruitment rates for a randomised controlled trial comparing propofol TCI to bolus administration. Methods: Four EDs in Scotland, UK, participated. Patients aged 18-65 years, with anterior shoulder dislocation, weight ≥ 50kg, fasted ≥ 90 min were screened. Patients underwent reduction of their dislocated shoulder using TCI propofol. The primary end point was patient satisfaction recorded on a Visual Analogue Scale. Results: Between 3 April 2017 and 31 December 2018, 25 patients were recruited with a recruitment rate of 20% for the 16-month recruitment window, with a temporary pause to allow amendment of drug dosage. Two patients were excluded. Twenty achieved adequate sedation, defined as a Modified Observer's Assessment of Alertness/Sedation Scale (OAA/S) 3. Successful reduction was achieved in all adequately sedated. Patient satisfaction was documented in 14 patients, mean±SD of 97±9 and time to sedation was 25±8 min. No adverse events were recorded using the Society of Intravenous Anaesthesia adverse event reporting tool. Conclusion: Propofol TCI was acceptable as a method of procedural sedation for patients. The lower than expected recruitment rates highlight the need for dedicated research support. Trial registration number: NCT03442803 .